The PHYSICOCHEMICAL AND FUNCTIONAL PROPERTIES OF STARCHES OF FLOUR OF CYCAS FRUITS OR “NTSAMBU” FROM COMOROS - Said Ali, Ibrahim; Ismael, Chakir; Mohamed, Anli; Razanamparany, Louisette (International Journal of Engineering Technologies and Management Research, 2024)
Cycads are archaic gymnosperms whose ovules provide almonds, highly valued in the diet by the ancestral populations of the Comoros. These almonds are essentially made up of 72% starch for 100 g of dry flour. Cycas fruit starches of comoros present appreciable physicochemical and functional properties. These starches are more digestible by α amylase compared to other flours such as potato flours. However, a significant fraction of resistant starch is present. The average amylose content (14% to 20%) suggests that these flours can be used in various cooking methods, such as for the production of porridges, cakes and for infant food. Their gelatinization temperature is between 73.5°C and 86.9°C. The reintegration of these fruits into the eating habits of the Comorians should contribute to limiting food security problems and thus promote a reappropriation of this resource by the Comorians and therefore preserve these Cycas unexploited or neglected by a large part of the Comorian population.